A Continuation of the Debate over Money and Totality. (1st April 2019) - Moseley, Fred
Abstract : This paper is a reply to David Laibman's latest paper critical of my 2016 book Money and Totality: A Macro-Monetary Interpretation of Marx's Logic in Capital and the End of the "Transformation Problem." This paper responds to the following points: did I misstate Laibman's position in my previous paper?; the logical priority of the production of surplus-value over the distribution of surplus-value (i.e., the prior determination of the total surplus-value); different starting points: quantities of money capital (Marx) vs. quantities of physical inputs and outputs (Sraffa); is Marx's theory "monetary"?; and (most importantly) is my interpretation of Marx's theory logically incoherent? I argue that Laibman's criticism of logical incoherence is based on the usual fundamental misinterpretation of Marx's transformation of values into prices of production—as a transformation from one set of micro prices (the values of individual commodities) to another set of micro prices (the prices of production of individual commodities). To the contrary, I argue that the logic of Marx's transformation is from macro total price to micro individual prices of production and that this macro-to-micro transformation is logically coherent, so there is no transformation problem in Marx's theory of prices of production .